Developing a UAE-Based Disputes Prediction Model using Machine Learning - Abu Laila, Ibrahim Wasef Subhi (2022)
A Master of Science thesis in Construction Management by Ibrahim Wasef Subhi Abu Laila entitled, “Developing a UAE-Based Disputes Prediction Model using Machine Learning”, submitted in April 2022. Thesis advisor is Dr. Sameh El-Sayegh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form)